Annoted Select Bibliography of Japanese Business and Trade Law in Western Languages - Baum, H; Nottage, L (Victoria University of Wellington Law Review, 1997)
This annotated bibliography updates Baum’s earlier bibliography in German. It comprises an annotated guide to general source material dating from around 1970, and a select bibliography of other works dating from around 1993. It includes a guide to useful sites on the Internet. As well as introducing and identifying publications in English, this bibliography aims to make more accessible some of the material increasingly available in other Western languages. It also includes the growing volume of writing on Japanese law emanating from Commonwealth countries.